PENGARUH MEDIA VIDEO PEMBERIAN PAKAN DAN AIR MINUM PADA UNGGAS PETELUR TERHADAP HASIL BELAJAR SISWA SMK - Juana Rikes Malaikosa (JUPI (Jurnal Pendidikan Indonesia), 2023)
This study aims to determine the influence of video media on student learning outcomes in learning to feed and drinking water in vocational students. This study used experiments using the research population in class X of SMK Negeri Bukapiting Alor East Nusa Tenggara. While the sample in this study was determined by cluster random sampling technique with a total of 40 students. Data collection using tests in the form of description questions. As for hypothesis testing using the ANOVA use spss technique. From the results of this study, it can be proven that there is an influence on learning feeding and drinking water using video media compared to learning feeding and drinking water without using digital media such as videos on the learning outcomes of vocational students